PENGEMBANGAN BAHAN AJAR DIGITAL MATEMATIKA SMA KELAS X BERORIENTASI HOTS - I Kadek Surya Atmaja; I Komang Sukendra; I Wayan Widana (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
HOTS learning is learning in the cognitive domain of analyzing, evaluating, and creating. This study aims to determine the development steps and quality of digital mathematics teaching materials for class X SMA HOTS oriented on the material of a three-variable linear equation system. This research and development procedure uses an adaptation of the Plomp model, with the following steps: initial investigation, design, realization/construction, and test, evaluation and revision. Sources of research data are validators and high school mathematics teachers. Research data collection techniques using a questionnaire. The results of the initial validity test were declared